2023
DOI: 10.1038/s44161-023-00294-y
|View full text |Cite
|
Sign up to set email alerts
|

Outlining cardiac ion channel protein interactors and their signature in the human electrocardiogram

Abstract: Protein–protein interactions are essential for normal cellular processes and signaling events. Defining these interaction networks is therefore crucial for understanding complex cellular functions and interpretation of disease-associated gene variants. We need to build a comprehensive picture of the interactions, their affinities and interdependencies in the specific organ to decipher hitherto poorly understood signaling mechanisms through ion channels. Here we report the experimental identification of the ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Understanding the role of the ion channel complex in the pathophysiology of neurological disease is still in its infancy and lagging behind the comprehension of cardiac dysfunctions. Recently, Maurya et al [ 99 ] identified protein interactants for 13 types of ion channels and established ion channel networks in murine and human heart tissues. Correlations were found in human population genetics data to specifically identify interacting proteins that influence the electrocardiogram [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the role of the ion channel complex in the pathophysiology of neurological disease is still in its infancy and lagging behind the comprehension of cardiac dysfunctions. Recently, Maurya et al [ 99 ] identified protein interactants for 13 types of ion channels and established ion channel networks in murine and human heart tissues. Correlations were found in human population genetics data to specifically identify interacting proteins that influence the electrocardiogram [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Maurya et al [ 99 ] identified protein interactants for 13 types of ion channels and established ion channel networks in murine and human heart tissues. Correlations were found in human population genetics data to specifically identify interacting proteins that influence the electrocardiogram [ 99 ]. Nevertheless, in neurons, AMPAR interacting partners regulating the number and function of AMPA receptors at the post-synapse, controlling synaptic strength and plasticity, have been often found in human patients suffering from schizophrenia or autistic spectrum disorders (see [ 100 ] for a review).…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to investigate the interactomes of trafficking-deficient K V 11.1 variants and compare them to WT K V 11.1 using AP-MS coupled with TMT labeling. Through this approach, we identified several proteins already known to interact with K V 11.1, such as the E3 ubiquitin ligase ( NEDD4L ), the four-and-a-half LIM domains protein 2 ( FHL2 ), the lectin-based folding chaperone calnexin ( CANX ) , caveolin 1 ( CAV1 ), and the 14-3-3ε protein ( YWHAE ) ( 26 , 27 , 38 , 39 , 40 , 41 ). The truncated variant interaction with 14-3-3ε was reduced compared to either WT or the full-length K V 11.1-G601S variant, consistent with previous work that suggests 14-3-3ε interacts with the C-terminal domain ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding reaffirms previous research highlighting age-related changes including both structural changes such as increased LV wall mass 43 , possibly driven by cardiomyocyte hypertrophy and functional changes such as the decline in diastolic function 24,44 . This decline in the CV may be driven by well-established age-related cellular and tissue level remodelling including impaired sodium channel function 44 (potentially though loss-of-function genetic mutations such as SCN5A as identified in previous ECG age-delta GWAS 45 and experimental studies 46 ) and the development of myocardial fibrosis 24,47 . It may also be affected by gap junction decoupling such as connexin 43 downregulation which is a known pathological remodelling in patients with ventricular hypertrophy and ischaemic heart diseases 48 .…”
Section: Discussionmentioning
confidence: 99%